Defensive transition process analysis. Defensive actions and behaviors associated with the recovery of the collective defensive organisation - Bastos, Mathias (2022)
The overall objective of the study is to identify the defensive behaviours that promote the recovery of defensive balance in the moments following the loss of the ball. The sample consists of 4209 defensive transition processes. All the actions analysed come from the 96 matches played during the group stage of the UEFA Champions League in the 2019/2020 edition. The observation tool is constituted by 15 categories and 88 indicators’ performance. All the indicators were analysed by a descriptive and bivariate analysis. Pot A teams have a more aggressive general approach to defensive recovery, with pressure from loss of ball; this may explain, that these teams conclude their defensive recoveries higher on the field. In relation with match status, winning teams lose the ball more regularly through the most offensive lines; and losing teams have a general approach to defensive recovery that ismore passive with a passive defense. Ball losses in the central lane, with a team block high on the field and stopping the opposing attacks far from his goal, are all important markers in order to reach the next round.